Effect of slaughter weight and breed on instrumental and sensory meat quality of suckling kids - Ripoll, G. (2013)
The effects of breed and slaughter weight on chemical composition, fatty acid groups, texture, and sensory characteristics of meat of 141 suckling male kids from 5 Spanish breeds were studied. There was a decrease in texture and lightness and hue angle with the increase of the slaughter weight. Fatty acid composition was correlated with the intramuscular fat content. All the breeds except MO had values of n−6/n−3 ratio below 4, which is the healthy limit recommended, and a low atherogenic index as well as a low intramuscular fat content. A multivariate analysis discriminated light kid, which had the most tender and juicy meat, from heavy kid which had more intense kid and milk odours. Blanca Andaluza and Pirenaica had most tender and juicy meat. The effect of slaughter weight on meat traits should be considered separately for each breed to find the most appropriate meat according to consumers preferences.